Kebijakan Online Single Submission sebagai E-Government dalam Mewujudkan Good Governance di Indonesia - Rahmi Ayunda; Nertivia Nertivia; Laode Agung Prastio; Octa Vila (Fakultas Hukum, Universitas Internasional Batam, 2021)
Based on the history before the reform era, there have been many cases of government committing corruption, collusion and nepotism, this is the background of the movement to create a government to run good governance. As time has progressed, the time has come for a time that is all full of digitalization, both in the economy, education and politics. This research uses normative legal research methods. This study shows that the government in running its government will also be based on the development of sophisticated information technology which can be called E-Government. Therefore, there is now a time when the Indonesian government has used and allowed the Online Single Submission (OSS) system to make it easier for people who want to take care of business licensing. The implementation of good governance during the Industry 4.0 Revolution can take advantage of science, technology and information to provide good facilities and services to the Indonesian people, and the public can easily access government information.